EFFECTS OF DEEP TILLAGE OF COTTON ROWS ON COTTON YIELD - Teshaboev Nodirbek Ikromjonovich; Murodov Umidjon Abdubaxrom ugʻli (Web of Journals Publishing, 2025)
Due to the belief that "the more cotton is grown between rows, the better the cultivation (chisel)", the deeper the softening of the rows will continue during the flowering period.
Keywords: Cotton, soil, tilling, chiseling, seed, moisture, cultivation, root, row spacing.